Ultraviolet radiation exposure to the face in patients with xeroderma pigmentosum and healthy controls: applying a novel methodology to define photoprotection behaviour. (24th February 2022) - Sarkany, R.P.E.; Canfield, M.; Morgan, M.; Foster, L.; Johnstone, K.; Sainsbury, K.; Araujo‐Soares, V.; Wulf, H.C.; Weinman, J.; Walburn, J.; Norton, S.
Summary: Background: In xeroderma pigmentosum (XP), the main means of preventing skin and eye cancers is extreme protection against ultraviolet radiation (UVR). Protection is most important for the face. Objectives: We aimed to assess how well patients with XP adhere to medical advice to protect against UVR by objectively estimating the mean daily dose of UVR to the face. Methods: We objectively estimated the UVR dose to the face in 36 patients with XP and 25 healthy individuals over 3 weeks in the summer. We used a new methodology which combined UVR dose measurements from a wrist‐worn dosimeter with an activity diary record of face photoprotection behaviour for each 15‐min period spent outside. A protection factor was associated with each behaviour, and the data were analysed using a negative binomial mixed‐effects model. Results: The mean daily UVR dose (weighted for DNA damage capacity) to the face in the patients with XP was 0·13 standard erythemal doses (SEDs) (mean in healthy individuals = 0·51 SED). There was wide variation between patients (range < 0·01–0·48 SED/day). Self‐caring adult patients had a very similar UVR dose to the face as cared‐for patients (0·13 vs. 0·12 SED/day), despite photoprotecting much more poorly when outside, because the self‐caring adults were outside in daylight much less. Conclusions: Photoprotection behaviour varies widely within the XP group indicating that nonadherence to photoprotection advice is a significant issue. The timing and duration of going outside are as important as photoprotective measures taken when outside, to determine the UVR exposure to the face. This new methodology will be of value in identifying the sources of UVR exposure in other conditions in which facial UVR exposure is a key outcome, particularly in patients with multiple nonmelanoma skin cancers. Abstract : Linked Comment: J.J. DiGiovanna and K.H. Kraemer. Br J Dermatol 2022; 186 :607–608. Plain language summary available online